Fundamentos para utilização dos smarthphones para o ensino de física - MIRANDA, Rodrigo Cezar Cordeiro de (2024)
The smartphone (smart phone) is an important utility in the daily lives of a large portion of the world's population, especially in urban areas. This paper aims to conclude the course through analyzes, studies and data prior to the subject addressed on the use of smartphones (mobile phones with mobile internet) by regular high school students and the need for their use by physics teachers in its pedagogical didactic methods and legal foundations brought by LDB, PNE and ECA. With this, it aims to bring this tool as pedagogical support for the teaching of physics. The results of these studies indicate that the smartphone is largely inserted in the daily lives of students, they use the devices for various forms of fun spend time and entertainment during classes, breaks and after classes. Therefore, students have developed methods and strategies of use not to be caught by teachers, where they have also made this technology an integral part of every moment of most young people's lives. Given this context we should be concerned to identify the possible solutions to require the use of these devices as a teacher educator tool, in this case for the teaching of physics. Making this the purpose of this work.